Helicobacter pylori infection and hyperemesis gravidarum: a prospective pilot study in India - V., Akhila M.; R., Padmasri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: About 80% of all pregnant women experience some form of nausea and vomiting during their pregnancy. Hyperemesis gravidarum, the commonest indication for admission to hospital in the first half of pregnancy affects approximately 0.3%-2.0% of pregnancies. Helicobacter pylori infection has been implicated in the cause of nausea and occasional vomiting in early pregnancy. The objectives of this study are to determine the proportion of H. pylori seropositivity among women with hyperemesis gravidarum (HG) and determine its relation with socio-economic status. Methods: This was a prospective study conducted in a tertiary hospital in Bangalore among 60 pregnant women with HG for a period of 12 months. Venous blood samples were obtained and serum IgG for H. pylori was measured using enzyme-linked immunosorbant assay (ELISA). Details regarding socioeconomic status, recurrence of symptoms and severity were noted. Results: The proportion of H. pylori seropositivity among pregnant women with hyperemesis in our study was 70%.There was a significant increase in severity and recurrence of vomiting among seropositive cases. Women belonging to rural areas had 1.17 times the risk of infection compared to women with urban area. We also found women belonging to the lower socioeconomic status had 0.52 times more risk to develop Helicobacter pylori infection. Conclusions: This study suggests that H. pylori is an independent risk factor for vomiting in pregnancy. Effective treatment and eradication of H pylori infection may help reduce severity and recurrence of vomiting among positive cases thus reducing its adverse consequences.